The 100th Birth Anniversary of the Great Man: Mihailo Marković (1923–2023): Marković and the role of the engaged intellectual - Govedarica, Milanko (Sociološki pregled, 2023)
The starting assumption is the opinion that Marković’s opus is quite relevant for the re-examination of the role of the socially engaged intellectual, particularly in regional and global circumstances today. The basic procedures in dealing with the topic are: (1) presentation of Marković’s main accomplishments, (2) analysis of the meaning and the place of the dialogue in communicative modalities of the opinion and (3) confirming the thesis about the harmful dialogue deficit through an illustrative example of the so-called collective West. The most important results refer to the explanation of the dissident and dialogue role of the socially responsible intellectual, as well as the corroboration of the opinions about Marković’s proper attitude in that respect.